EFEK UDARA DI DALAM SISTEM REFRIGERASI - Patabang, Daud (MEKTEK, 2005)
The performance of refrigeration system are affected by  condenser, evaporator ,compressor and regulating  valve. Besides   cooling system itself   air in the system are also considered to the performance. The aim of this research to investigate the effect of air in the refrigeration system that  cause the performance of system. The result of this research indicates that coefficient of performance (COP)decrease falls to 37 % (from 8.4 to 5.28) due to the air in refrigerations system, on the contrary  there  is increasing about 40 % (from 25 kJ/kg to 35 kJ/kg)of energy in gernerating compressor